2017
DOI: 10.1186/s12199-017-0609-8
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in plasma free amino acid levels and its association with gout

Abstract: BackgroundStudies on the association of plasma-free amino acids with gout are very limited and produced conflicting results. Therefore, we sought to explore and characterize the plasma-free amino acid (PFAA) profile in patients with gout and evaluate its association with the latter.MethodsData from a total of 819 subjects (including 34 patients with gout) undergoing an annual health examination program in Shimane, Japan were considered for this study. Venous blood samples were collected from the subjects and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Certain amino acids participate in the biosynthesis of purine and the subsequent formation of UA 23 . In this context, we recently showed that plasma levels of several branched chain amino acids (BCAAs) and aromatic amino acids (AAAs) had significant positive associations with gout, a disease with elevated levels of UA in the blood 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Certain amino acids participate in the biosynthesis of purine and the subsequent formation of UA 23 . In this context, we recently showed that plasma levels of several branched chain amino acids (BCAAs) and aromatic amino acids (AAAs) had significant positive associations with gout, a disease with elevated levels of UA in the blood 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Glycine has been reported to negatively correlate with gout in other metabolic studies 26 . It is involved in purine metabolism and is a precursor of uric acid 26 .…”
Section: Resultsmentioning
confidence: 84%
“…AminoIndex™ technology was originally developed to screen various types of diseases, such as cancer [1,7,15,16], hepatic or renal failure [17], cardiovascular and metabolic disorders [18][19][20], and others [21].…”
Section: Discussionmentioning
confidence: 99%